Global overview of government-endorsed nutrition labeling policies of packaged foods: a document review - Afroza, Ummay; Abrar, Ahmad Khairul; Nowar, Abira; Sobhan, Sheikh Mohammad Mahbubus; Ide, Nicole; Choudhury, Sohel Reza (Frontiers in Public Health, 2024)
Introduction Nutrition labeling provides nutritional information about nutrients present in a food product. It is commonly applied to packaged foods and beverages, where the information can be presented on the back or front of the pack as the nutrient declaration, nutrition and health claims, and supplementary nutrition information. Nutrition labeling is an important policy instrument for improving the nutritional quality of foods and promoting healthy diets, as it allows consumers to make informed purchasing decisions. This document review aims to provide a comprehensive overview of government-endorsed nutrition labeling policies related to nutrient declaration, nutrition claims, and supplementary nutrition information enforced worldwide. Methods We searched two nutrition policy databases, the Global database on the Implementation of Food and Nutrition Action (GIFNA) and the NOURISHING database, and government websites of some selected countries for the government-endorsed nutrition labeling policies published up to June 2023. We narrated the policy adopting countries' distribution by WHO regions, mode of implementation (voluntary or mandatory), and types of front-of-pack labels implemented. Results Globally, we found that 95 countries have mandatory policies for nutrient declarations on packages of processed products. These include 41 countries in Europe, 19 in America, 14 in the Western Pacific, nine in Africa, seven in the Eastern Mediterranean region, and five countries from South-East Asia. Additionally, 71 countries have policies on the use of nutrient claims like “fat-free,” “excellent source,” and “fortified.” European region has the highest number of countries (37) that have rules on nutrient claims. Front-of-pack labeling (FOPL) policies have been introduced in 44 countries as supplementary nutrition information. Of these, 16 countries have adopted FOPL as mandatory, while others have implemented it voluntarily. The FOPL systems include warning labels, keyhole logo, health star rating, traffic light labeling, nutri-score, and healthy choice logos. Conclusion Over recent years, the number of countries adopting mandatory nutrition labeling policies, especially FOPLs, has increased globally. Labeling policies should be evidence-based and follow the best practices to protect consumers from unhealthy nutrients and promote healthy eating. FOPL designs need to be selected based on country-specific evidence of effectiveness and appropriateness, avoiding industry influence.